Creep–fatigue interaction behavior of nickel-based single crystal superalloy at high temperature by in-situ SEM observation. (December 2020) - Wang, Zhen; Wu, Wenwang; Liang, Jiecun; Li, Xide
Highlights: Creep-fatigue tests were performed in an in-situ SEM platform at 900 °C. An abnormal behavior of cycle life was observed and explained by dislocation structure theory. The transition of crack growth mode with different dwell time was analyzed. CTOD was used to characterize the creep-fatigue small crack growth rate. Abstract: Creep-fatigue interaction behavior of nickel-based single crystal superalloy was studied in an in-situ SEM platform at 900 °C. Dwell times of 15, 30, 60, 90, 120 s were introduced at the tensile peak stress of each cycle. Experimental results showed that the life cycles firstly decreased rapidly then slightly increased with the increasing dwell time, which was explained by the accumulated inelastic strain. Dislocation microstructure and inelastic strain were correlated for different dwell time by TEM analysis. Crack propagation mode transition was analyzed. Comparing with the stress intensity factor amplitude, crack tip opening displacement was more suitable for characterizing the creep-fatigue small crack growth rate.